Comparative study of the potentiating effect of isoflurane and sevoflurane on the duration of muscle relaxation during surgical interventions in one-day surgery in children. - E. M. Nasibova (Pediatric Anesthesia and Critical Care Journal, 2021)
The potentiating effect of various drugs used in anesthe- siology, especially if this interaction is related to analge- sic, hypnotic and muscle relaxant components, is always of interest for the development and implementation of new techniques of general anesthesia. Therefore, the pur- pose of our study was to carry out a comparative assess- ment of the potentiating effect of modern inhalation an- esthetics on the duration of muscle relaxants used in one- day surgery in children. The study was conducted in AMU surgical clinics from 2010 to 2020. The study in- cluded 156 children aged 0 to 16 years of age at risk of I- II ASA anesthesia, who were operated on in a planned manner under combined general anesthesia. The study showed that atracurium besylate provided almost the same, with a high degree of predictability, the duration of deep neuromuscular blockade in children, regardless of age - which makes it the drug of choice for children in the first year of life. In cisatracurium besylate and rocu- ronium bromide, it was noted that the duration of deep neuromuscular blockade in children under 2 years of age is significantly longer than in older children. The shortest duration of action of rocuronium bromide was noted in children over 2 years of age when compared with atracu- rium and cisatracurium (p <0.01). This fact makes it the main drug for providing myoplegia in children of this age with short-term surgical interventions. Keywords Sevoflurane, isoflurane, rocuronium bromide Introduction Recently, for a number of reasons, including economic ones, interest in inhalation anesthesia, which has long been the most widespread in the world, has been reviving. The potentiating effect of various drugs used in anesthe- siology, especially if this interaction is related to analge- sic, hypnotic and muscle relaxant components, is always of interest for the development and implementation of new techniques of general anesthesia. Especially, the muscle relaxant effect of modern inhalation anesthetics prompted us to conduct this study. Aim of the study: to conduct a comparative assessment of the potentiating effect of modern inhalation anesthetics on the duration of muscle relaxants used in one-day sur- gery in children. Material and Methods The research was carried out in the surgical clinics of the AMU in the period from 2010 to 2020. The study in- cluded 156 children aged 0 to 16 years of age at risk of I- II ASA anesthesia, who were operated on in a planned manner under combined general anesthesia. In accord- ance with the requirements of the international program GCP (good clinical practice), all patients were included in the study only after receiving the voluntary consent of their parents. The criteria for excluding patients from the